Metamaterial foam core sandwich panel designed to attenuate the mass-spring-mass resonance sound transmission loss dip. (May 2020) - de Melo Filho, N.G.R.; Claeys, C.; Deckers, E.; Desmet, W.
Highlights: STL improvement of foam core double panels using resonant metamaterials. Mass-spring-mass STL deterioration effect is attenuated using resonant metamaterials. Fast STL prediction method using Heckl's model and metamaterials dynamic mass. Good agreement between numerical predicted and experimental results. Abstract: Double panel partitions with a foam core suffer a poor sound transmission loss at their mass-spring-mass resonance frequency. This paper considers the use of vibro-acoustic resonant metamaterials to improve the acoustic insulation performance at the frequency region of this resonance while adding only 8% of mass to the double panel, hence maintaining its lightweight characteristics. To design the metamaterial, dispersion curves are calculated through finite element unit cell analysis to predict the stop band frequency region. The resulting sound transmission loss due to the stop band effect is predicted using Heckl's model combined with the equivalent dynamic mass of the metamaterial, which is obtained from the dispersion curves analysis. This method allows taking into consideration complex resonator geometries and locally reacting material interlayers in the hosting panel. The designed metamaterial double panel is realised, and its experimentally measured insertion loss surpasses the insertion loss of the bare and equivalent mass addition double panels in the targeted frequency region. The predicted insulation agrees well with the measured performance, validating the proposed method.